The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fendo.2023.1177547
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis and its potential role in gestational diabetes mellitus: updated evidence from pathogenesis to therapy

Yan Zhao,
Qianqian Gao,
Baoxuan Li
et al.

Abstract: BackgroundStudies have demonstrated that high iron status is positively associated with gestational diabetes mellitus (GDM), implying that iron overload and ferroptosis play important roles in the development of GDM. The aim of this study was to explore effective therapeutic drugs from traditional Chinese medicine (TCM)formulas for the treatment of GDM based on ferroptosis.MethodsIn this study, the presence of ferroptosis in the placenta was verified through clinical and experimental data, and key genes were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“… 14 Recently, there has been emerging evidence supporting the involvement of ferroptosis in patients with gestational diabetes mellitus (GDM) and the possible modulatory roles of ferroptosis-related genes in the molecular mechanisms of GDM. 15 Yifang Zheng et al found that correcting the imbalance of fatty acid oxidation/peroxide-induced ferroptosis could ameliorate placental injury in GDM. 16 Studies have also suggested that targeting ferroptosis may be a potential therapeutic approach for treating GDM.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Recently, there has been emerging evidence supporting the involvement of ferroptosis in patients with gestational diabetes mellitus (GDM) and the possible modulatory roles of ferroptosis-related genes in the molecular mechanisms of GDM. 15 Yifang Zheng et al found that correcting the imbalance of fatty acid oxidation/peroxide-induced ferroptosis could ameliorate placental injury in GDM. 16 Studies have also suggested that targeting ferroptosis may be a potential therapeutic approach for treating GDM.…”
Section: Introductionmentioning
confidence: 99%